Desempeño laboral de los funcionarios del Gobierno Autónomo Descentralizado Parroquial Rural La Esmeralda - González Camacho, Wagner Valdemar (2019)
The work performance is very significant in a company because, although there is an organizational and institutional structure, if there is no appropriate communication system for all areas, the best work environment cannot be obtained and the results will be frustrating, with this It is observed that the progress of an employee within a structure will be restricted by the incorrect information he receives and this will cause him to work in a poor manner and the desired results that are required for the proper functioning of the same cannot be achieved. The strategic design for a good work performance is to build a good work environment and have clear objectives to improve the performance that is supposed to integrate the organization, modifying elements that place the Rural Decentralized Autonomous Government of La Esmeralda Rural Parish in a clear perspective, as well as put to the employee in a state open to receiving information to achieve their best progress and achieve the welfare of the institution